PENERAPAN MODEL PEMBELAJARAN INQUERY UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 023 LUBUK JAWI BAGANBATU Ety - Desriana, Ety; Antosa, Zariul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research study IPS poor performance of students, with an average of 66.07. While the value of minimum completeness criteria (KKM) IPS is 75. The subjects of this study consisted of 28 students 13 men 15 women. Of the 28 students only 10 who reached the KKM. This study uses the design of classroom action research conducted during two cycles of the study This study is a Class Action Research (CAR) conducted aims to improve learning outcomes IPS Elementary School fourth grade students 023 Lubuk Jawi Baganbatu by implementing cooperative learning model inquery. The problems in this study is whether the implementation of cooperative learning model inquery can improve learning outcomes IPS Elementary School fourth grade students 023 Lubuk Jawi Baganbatu? The research was conducted from April to May 2016. From the analysis of research data visible increase in the percentage of teachers in learning activities. In the first cycle the first meeting 64.29%, at the end of the cycle exactly at the meeting to two second cycle of teacher activity increased to 92.86%. While the percentage of student activity in the first cycle of the first meeting of 57.14% was also increased in the second meeting of the second cycle into 85.71%. The increased activity of teachers and students also have an impact on student learning outcomes from an average score of 66.07 at baseline to 74.46 with the percentage increase of 8.39%. Thus during the second implementation cycle of this study indicate that the application of cooperative learning model inquery can improve learning outcomes IPS Elementary School fourth grade students Baganbatu 023 Lubuk Jawi.Key Words: Cooperative inquery model, IPS Learning Outcomes